Aspek Perkembangan pada Anak Sekolah Dasar: Masalah dan Perkembangannya - Umi Latifah (Universitas Islam Negeri Raden Mas Said Surakarta, 2017)
This article is intended to analyze the seven aspects of the development of elementary school children. This research uses the descriptive qualitative method, the data collected by interviewing 8 students of the sixth grade in MI 2 Darsussalam. The results were then analyzed using the theoretical study on the seven aspects of the development of elementary school children. The results showed that seven aspects of development affect the learning process in the classroom. These aspects of development are also influenced by genetic factors, family environment, and the playing environment children. Thus, it is important for parents to monitor aspects of child development to grow into an accomplished individual.Keywords:developmental aspect, elementary school, problems